Prevalence of developmental anomalies of teeth in a group of North Karnataka population, India - Javali, Rajeshwari; Meti, Mangala (International Journal of Dental Research, 2015)
Aims and objective: To assess the prevalence of the developmental dental anomalies like disturbances in size, shape, structure, eruption pattern and number in a group of North Karnataka population and to assess the dental anomalies in patients with head and neck syndrome.Method: A cross-sectional prospective survey was carried out at P.M.N.M Dental College and Hospital, Bagalkot, North Karnataka, India during the academic year, November 2011 to August 2013 to study the prevalence of various developmental dental anomalies of teeth in a population of 3000 patients aged between 10 to 30 years in both genders. Patients were screened clinically for the presence of dental anomalies with appropriate radiographs and dental casts.Result: Of 3000 patients screened, 477 had developmental dental anomalies. Out of these, 254 were males and 223 were females. The most commonly found anomalies were impacted teeth, hypodontia, dental fluorosis, overretained, supernumerary teeth, talon’s cusp with the least being dentinogenesis imperfecta (none).Conclusion: The significance of conducting such a study is, that if the dental anomalies are detected earlier, the consequences (like early pulp involvement in dens-in-dente, malocclusion) can be intervened and treated accordingly. This study hence provides an useful data regarding the prevalence of the most and the least common anomalies in North Karnataka region of India.